(untitled) (Hungarian Journal of Industry and Chemistry, 2010)
I present an automatic assembly system in this article. I search out the main methods of assembly first. Than I describe the system found in the Department of Production Engineering at the University of Miskolc. Next I choose one of the used robots, and I describe it from the viewpoint of productivity and flexibility.